Extensive morphological and behavioural diversity among fourteen new and seven described species in Phytophthora Clade 10 and its evolutionary implications - Jung, T; Milenković, I; Corcobado, T; Májek, T; Janoušek, J; Kudláček, T; Tomšovský, M; Nagy, Z Á; Durán, A; Tarigan, M; Sanfuentes von Stowasser, E; Singh, R; et al. (Persoonia, 2022)
During extensive surveys of global Phytophthora diversity 14 new species detected in natural ecosystems in Chile, Indonesia, USA (Louisiana), Sweden, Ukraine and Vietnam were assigned to Phytophthora major Clade 10 based on a multigene phylogeny of nine nuclear and three mitochondrial gene regions. Clade 10 now comprises three subclades. Subclades 10a and 10b contain species with nonpapillate sporangia, a range of breeding systems and a mainly soil- and waterborne lifestyle. These include the previously described P. afrocarpa, P. gallica and P. intercalaris and eight of the new species: P. ludoviciana, P. procera, P. pseudogallica, P. scandinavica, P. subarctica, P. tenuimura, P. tonkinensis and P. ukrainensis. In contrast, all species in Subclade 10c have papillate sporangia and are self-fertile (or homothallic) with an aerial lifestyle including the known P. boehmeriae, P. gondwanensis, P. kernoviae and P. morindae and the new species P. celebensis, P. chilensis, P. javanensis, P. multiglobulosa, P. pseudochilensis and P. pseudokernoviae. All new Phytophthora species differed from each other and from related species by their unique combinations of morphological characters, breeding systems, cardinal temperatures and growth rates. The biogeography and evolutionary history of Clade 10 are discussed. We propose that the three subclades originated via the early divergence of pre-Gondwanan ancestors > 175 Mya into water- and soilborne and aerially dispersed lineages and subsequently underwent multiple allopatric and sympatric radiations during their global spread. Citation: Jung T, Milenković I, Corcobado T, et al. 2022. Extensive morphological and behavioural diversity among fourteen new and seven described species in Phytophthora Clade 10 and its evolutionary implications. Persoonia 49: 1-57. https://doi.org/10.3767/persoonia.2022.49.01.
Keywords: evolution; Laurasia; phylogeny; Gondwana; allopatric; radiation; sympatric; biogeography; Oomycete